Jurisdiction Over Underwater Cultural Heritage in the EEZ and on the Continental Shelf: A Perspective From the Practice of States Bordering the South China Sea. (3rd July 2019) - Lin, Zhen
Abstract: The Chinese initiative of constructing the 21st Century Maritime Silk Road could be identified as a new chance to promote the protection of underwater cultural heritage (UCH) in the South China Sea. However, uncertainties concerning the jurisdictional issue over the UCH in the exclusive economic zone (EEZ) or on the continental shelf constitute an obstacle. The Convention on the Protection of Underwater Cultural Heritage has, to some extent, enlarged the coastal state's jurisdiction. State practice differs on this issue. This article focuses on the domestic legislations of states bordering the South China Sea related to the jurisdiction over UCH found in their EEZ or on their continental shelf.